Measurement of Stigma and Relationships Between Stigma, Depression, and Attachment Style Among People with HIV and People with Hepatitis C - Cabrera, Christine M. (Université d'Ottawa / University of Ottawa, 2014)
This dissertation is composed of three studies that examined illness-related stigma, depressive symptoms and attachment style among patients living with HIV and Hepatitis C (HCV). The first study examined the psychometric properties of a brief HIV Stigma Scale (B-HSS) in a sample of adult patients living with HIV (PHA) (n=94). The second study developed and explored the psychometric properties of the HCV Stigma Scale in a sample of adult patients living with HCV (PHC) (n =92). Psychometric properties were evaluated with classical test theory and item response theory methodology. The third study explored whether illness-related stigma mediated the relationship between insecure attachment styles (anxious attachment or avoidant attachment) and depressive symptoms among PHA (n =72) and PHC (n=83). From June to December 2008, patients were recruited to participate in a questionnaire study at the outpatient clinics in The Ottawa Hospital. Findings indicated that the 9-item B-HSS is a reliable and valid measure of HIV stigma with items that are highly discriminatory, which indicates that items are highly effective at discriminating patients with different levels of stigma. The 9-item HCV Stigma Scale was also found to be reliable and valid with highly discriminatory items that effectively differentiate PHC. Construct validity for both scales was supported by relationships with theoretically related constructs: depression and quality of life. Among PHA, when HIV stigma was controlled the relationship between anxious attachment style and depression was not significant. However, the relationship between avoidant attachment style and depressive symptoms decreased but remained significant. Among PHC when HCV stigma was controlled the relationship between insecure attachment styles and depressive symptoms was not significant. Dissertation results emphasize the importance of identifying patients experiencing illness-related stigma and the relevance of addressing stigma and attachment style when treating depressive symptoms among PHA and PHC.
Keywords: HIV Stigma; HCV Stigma; Item Response Theory; Attachment Theory